Design Tradeoffs in CXL-Based Memory Pools for Public Cloud Platforms - Berger, Daniel S.; Li, Huaicheng; Zardoshti, Pantea; Shah, Monish; Rajadnya, Samir; Lee, Scott; Hsu, Lisa; Agarwal, Ishwar; Hill, Mark D.; Bianchini, Ricardo (IEEE Micro, 2023)
DRAM is a key driver of performance and cost in public cloud servers. At the same time, a significant amount of DRAM is underutilized due to fragmented use across servers. Emerging interconnects such as CXL offer a path towards improving utilization through memory pooling. However, the design space of CXL-based memory systems is large, with key questions around the size, reach, and topology of the memory pool. At the same time, using pools requires navigating complex design constraints around performance, virtualization, and management. This paper discusses why cloud providers should deploy CXL memory pools, key design constraints, and observations in designing towards practical deployment. We identify configuration examples with significant positive return of investment.